Spatiotemporal Changes in Catch Composition of Marine Species Across Seawater Temperature Shift Points in Korean Water - Hyithaek Ceong; Inyeong Kwon (Animals)
This study aimed to evaluate the effects of water temperature and catch frequency on biodiversity and distribution in the waters around Korea. We analyzed spatiotemporal catch data reported by fishermen and evaluated the fluctuations in the dominantly caught species based on the timing of the water temperature changes between 1999 and 2021. This study found an upward trend in the water temperature, and species diversity increased in the East, West, and South Seas after the water temperature changed. Relatively stable species diversity was maintained in the East Sea/Sea of Japan, although variability increased significantly in the West and South Seas. The distribution in the caught species showed that Octopodidae spp. and Ommastrephidae spp. were increasingly caught more consistently alongside Pleuronectidae spp. Moreover, this dominance was maintained even after the change in water temperature and was shown to be relatively less sensitive to water temperature changes.